Thirty Years of Advertising Research in Leading Communication and Marketing Journals: Learning From the Parent Disciplines. Issue 1 (2nd January 2017) - Avant, J. Adam; Kim, Kyongseok; Hayes, Jameson L.
ABSTRACT: Academic advertising research has been criticized for a lack of progression and change. The criticism has revolved around the fact that advertising research has heavily relied on theories and methodologies from its parent disciplines such as psychology, communication, and marketing. To identify potential venues for progression and provide a complete understanding of academic advertising research, a longitudinal content analysis was conducted with scholarly advertising articles from twelve major communication and marketing journals from 1980 to 2010. This analysis seeks to suggest possible routes to moving advertising research forward by juxtaposing its research approach to that of broader marketing and communications journal research.